ANALYSIS OF CAUSAL FACTORS AND TEACHER EFFORTS IN OVERCOMING BEGINNING READING DIFFICULTIES OF GRADE 1 ELEMENTARY SCHOOL STUDENTS: Analisis Faktor Penyebab dan Upaya Guru Dalam Mengatasi Kesulitan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Fina Faiqotul Ulya; Ika Ari Pratiwi; Rani Setiawaty (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research was motivated by the condition of first-grade students at SDN Ngepungrojo 01 who still experience difficulties in early reading skills, particularly in recognizing letters, spelling words, and blending letter sounds. This study aims to analyze the factors causing early reading difficulties and to describe the teacher’s efforts in overcoming these difficulties among first-grade elementary school students. This study employed a qualitative research method with a case study approach. The participants consisted of one first-grade teacher and six students who experienced reading difficulties out of a total of 26 students in the class. Data were collected through observation, interviews, and documentation. The data were analyzed through the stages of data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The results showed that early reading difficulties were influenced by three main factors: intellectual, environmental, and psychological factors. Intellectual factors were related to students’ ability to recognize letters and blend sounds into syllables. Environmental factors were associated with limited learning support and reading habits at home. Psychological factors included low interest, motivation, and concentration in reading activities. The teacher’s efforts to address these difficulties included the use of singing methods, letter card media, drill methods, additional guidance, and communication with parents. The findings of this study provide practical implications for teachers in designing more appropriate instructional strategies to help students overcome early reading difficulties.